New developments in the optometrist’s assessment and treatment of common headaches - Maduabuchukwu Innocent Nkollo; Aghogho Odogu (Advances in Medical, Pharmaceutical and Dental Research)
Headache is pain experienced in the head and neck. It varies in types as it is caused by several reasons but is chiefly of two types, primary and secondary headaches. Primary headaches have no known cause, but secondary headaches have several causes. Tension, cluster and Migraine headaches are examples of primary headaches but hormonal, allergies, caffeine, exertional, hypertension, rebound, post-traumatic and headaches of ocular origin are secondary headaches. Primary and secondary headaches have their respective presentations, signs and symptoms. These headaches also have their peculiar management plans which have been addressed in this article. However, it is expected that the Optometrist will carry out the required eye examination procedures and/or prescribe the ideal medications, if need be, to remedy the headache complaint.   Received on, 01 December 2024 Accepted on, 02 January 2025 Published on, 30 January 2025